Partial Agonists and Dual Disorders: Focus on Dual Schizophrenia - Peris, Lola; Szerman, Nestor (Frontiers in Psychiatry, 2021)
Dual disorder is a term applied to patients with an addictive disorder and other mental disorder. Epidemiological studies have established that dual disorders are an expectation rather than an exception. They are difficult to diagnose and treat and constitute a huge burden for both patients and their relatives and society. Current treatments are a combination of those needed to treat the addictive disorder with those focused on the co-occurring psychiatric disorder. Focusing specifically on schizophrenia, growing scientific evidence supports the existence of a shared vulnerability for substance use in these patients and those at risk. Various antipsychotics have been found to be useful in the treatment of psychotic symptoms and disorders; however, few effective treatments have been identified until now for substance use disorders in patients with dual schizophrenia. Partial agonism stands as a new pharmacological option available in recent years. Molecules with this kind of action may act as functional agonists or as antagonists, depending on the surrounding levels of the neurotransmitter. Studies have found their efficacy in schizophrenia, addiction, anxiety and depression. Certain partial agonist antipsychotics seem to have a role in the treatment of dual schizophrenia. That could be the case with cariprazine. Because of its higher affinity for dopaminergic D3 receptors compared to D2, a potential to prevent relapse to addiction, added to its antipsychotic efficacy, has been suggested. Here we briefly review current advances and future directions and introduce some personal insights into the role of partial agonists in co-occurring schizophrenia and substance use.